Lipid droplet growth: regulation of a dynamic organelle. (August 2017) - Barneda, David; Christian, Mark
Highlights: Lipid droplet fusion involves major changes in the LD membrane components. Phosphatidic Acid is a key regulator of LD dynamics. Adipocyte differentiation invokes profound regulation of lipid droplet proteins. Transitions between white and BRITE adipocytes require lipid droplet remodelling. Abstract : Intracellular lipid droplets (LDs) are remarkably dynamic and complex organelles that enact regulated storage and release of lipids to fulfil their fundamental roles in energy metabolism, membrane synthesis and provision of lipid-derived signaling molecules. Although small LDs are observed in all types of eukaryotic cells, it is adipocytes that present the widest range of sizes up to the massive unilocular droplet of a white adipocyte. Our knowledge of the proteins and associated processes that control LD dynamics is improving. The dynamic expression of LD-associated proteins is vital for controlling LD biology and is most apparent during adipocyte differentiation. Recent findings on the molecular mechanisms of lipid droplet enlargement reveal the importance of distinct functional groups of proteins and phospholipids.